Respiratory Ammonification of Nitrate Coupled to Anaerobic Oxidation of Elemental Sulfur in Deep-Sea Autotrophic Thermophilic Bacteria - Slobodkina, Galina B.; Mardanov, Andrey V.; Ravin, Nikolai V.; Frolova, Anastasia A.; Chernyh, Nikolay A.; Bonch-Osmolovskaya, Elizaveta A.; Slobodkin, Alexander I. (Frontiers in Microbiology, 2017)
Respiratory ammonification of nitrate is the microbial process that determines the retention of nitrogen in an ecosystem. To date, sulfur-dependent dissimilatory nitrate reduction to ammonium has been demonstrated only with sulfide as an electron donor. We detected a novel pathway that couples the sulfur and nitrogen cycles. Thermophilic anaerobic bacteria Thermosulfurimonas dismutans and Dissulfuribacter thermophilus, isolated from deep-sea hydrothermal vents, grew autotrophically with elemental sulfur as an electron donor and nitrate as an electron acceptor producing sulfate and ammonium. The genomes of both bacteria contain a gene cluster that encodes a putative nitrate ammonification enzyme system. Nitrate reduction occurs via a Nap-type complex. The reduction of produced nitrite to ammonium does not proceed via the canonical Nrf system because nitrite reductase NrfA is absent in the genomes of both microorganisms. The genome of D. thermophilus encodes a complete sulfate reduction pathway, while the Sox sulfur oxidation system is missing, as shown previously for T. dismutans. Thus, in high-temperature environments, nitrate ammonification with elemental sulfur may represent an unrecognized route of primary biomass production. Moreover, the anaerobic oxidation of sulfur compounds coupled to growth has not previously been demonstrated for the members of Thermodesulfobacteria or Deltaproteobacteria, which were considered exclusively as participants of the reductive branch of the sulfur cycle.